Coherent Contention Resolution Diversity Slotted ALOHA: An Improved Multiple Access Method for Satellite IoT System - Liu, Ziwei; Zhu, Tiantian; Zhang, Chen; Zhang, Gengxin; Zhao, Shanshan (Frontiers in Space Technologies, 2021)
For Beyond 5G/6G system, satellite communication systems become an effective component of the space and terrestrial integrated network. Among typical applications, massive Machine Type of Communication (mMTC) is a promising and challenging application. The demands of low power consumption and light signaling make random access methods as the potential solution. Up to now, contention resolution-based ALOHA methods, such as contention resolution diversity slotted ALOHA (CRDSA), improve the throughput significantly. However, its throughput will meet the inflection point soon with the normalized load increasing since collisionless packets are hardly existing. In fact, the diversity of transmitting packets is not utilized totally. In this paper, an improved random access method, named coherent CRDSA method (C-CRDSA), is proposed. It accumulates replicated packets coherently at receiver and further improve the throughput over CRDSA. Detailed derivations and simulations are given. Simulation results corroborate the effectiveness of the proposed method.